Watching television in contemporary polish villages - Woźniak, A. (Матеріали до української етнології, 2012)
Today’s cultural landscape of Polish villages is shaped definitely by media, especially television. The discussion about the role of this medium in creating culture by showing different cultural patterns and lifestyles is very important. Although some question its cultural mission, arguing that its nature compels viewers to passivity, others note that because there are many interpretations of its programs or films, it proves that watching TV is an active process. In my presentation I would like to show why Polish soap operas and telenovelas were important factors in creating villages’ cultural landscape. After doing anthropological research (2005–2008), I observed that the most popular TV programs are serials: soap operas and telenovelas. I wondered why they had been watched by almost all members of local communities and what they really had meant for them?